2016
DOI: 10.1590/1676-0611-bn-2015-0133
|View full text |Cite
|
Sign up to set email alerts
|

Past and present land use influences on tropical riparian zones: an isotopic assessment with implications for riparian forest width determination

Abstract: In this article, by using carbon stable isotopes, we assessed the past and present land use influences that riparian areas are subject within agricultural landscapes. Emphasis is given to the understanding of the effects of the 2012 Brazilian Forest Act on such areas. We selected five riparian areas within a highly C4 dominated agricultural landscape. Three of them had 30 meters native riparian forest buffer (NRFB) and two of them had 8 meter and no NRFB. We used three 100 meter-transects located 5, 15 and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…This change was reflected in the higher percentage of consolidated APPs found for this APP type (34% of the total consolidated APPs), as shown in Table 4. The reduced width of up to 5 m that need to be restored around rivers (in the case of properties up to 1 FM) was considered insufficient for maintaining ecosystem services [34][35][36].…”
Section: Implications For Itacaiúnas Watershed Managementmentioning
confidence: 99%
“…This change was reflected in the higher percentage of consolidated APPs found for this APP type (34% of the total consolidated APPs), as shown in Table 4. The reduced width of up to 5 m that need to be restored around rivers (in the case of properties up to 1 FM) was considered insufficient for maintaining ecosystem services [34][35][36].…”
Section: Implications For Itacaiúnas Watershed Managementmentioning
confidence: 99%
“…Stable-isotope forensic studies have sporadically been used in Brazil. δ 15 N and δ 13 C helped to identify the origin of Brazilian marijuana seized , to trace origin and effect of illegal discharge of residues in streams and sediment (Barbieri et al, 2014;Roth et al, 2016), but also for an isotopic assessment to help understand the effects of the 2012 Brazilian Forest Act on tropical riparian zones (Salemi et al, 2016).…”
Section: Potential Use Of Isoscapes In Brazilmentioning
confidence: 99%
“…Very few studies using δ 13 C spatial patterns have been employed to measure land-use effects in aquatic (Sanaiotti et al, 2002;Augusto et al, 2015) and terrestrial ecosystems (Assad et al, 2013;Salemi et al, 2016;Figueira et al, 2016), which, therefore, might closely fit what has been applied in Brazil in terms of the isoscape approach in any published study led by Brazilian research groups.…”
Section: Potential Use Of Isoscapes In Brazilmentioning
confidence: 99%
“…It is expected that these vegetation strips protect against stream bank erosion ( Martin and Church, 2000;McKergow et al, 2003;Zaimes et al, 2008;Zaimes and Schultz, 2015) and protect water bodies against pollution, by trapping a large fraction of the soil particles and runoff originating from arable land (Bussi et al, 2016;Dosskey et al, 2010;Zhang et al, 2010). However, recent studies have shown that trapping under field conditions is often considerably lower than anticipated from laboratory or experimental plots results due the formation of preferential pathways within the buffer strips that may reduce their buffering capacity (Knight et al, 2010;Salemi et al, 2016;Stehle et al, 2016;Wallace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%